Animal behavior informed by history: Was the Asiatic cheetah an obligate gazelle hunter? - Mohammad S Farhadinia; Bagher Nezami; Ali Ranjbaran; Raul Valdez (PLoS ONE, 2023)
Understanding key ecological adaptations, such as foraging, when a predator is almost extinct is complex. Nonetheless, that information is vital for the recovery of the persisting individuals. Therefore, reviewing historical, ethnobiological and recent records can assist in exploring the species behavioral ecology. We applied this approach to Asiatic cheetahs (Acinonyx jubatus venaticus), which once roamed most west and central Asian countries but now is confined to a few dozens in Iran, at historical (pre-1970) and recent (post-1970) scales. We addressed a widely popular perception that Asiatic cheetahs were subjected to prey shifts from gazelles (Gazella spp.) in open plains areas to urial (Ovis vignei) in mountains because of gazelle populations declines due to anthropogenic influences. We also quantified recent prey choice of Asiatic cheetahs and their behavioral plasticity in foraging different prey species types. Although ethnobiological and historical records suggested that gazelle species were the main prey for cheetahs across their Asian range. However, urial were also commonly reported to be hunted by cheetahs across their historical Asian range, showing that the predation on mountain ungulates is not an emerging hunting behavior in Asiatic cheetahs. We found spatiotemporal plasticity in recent hunting behavior of cheetahs with selective predation on adult urial males. There was temporal overlap in hunting times for plains dwelling versus mountain ungulates, albeit with some minor differences with morning mostly for gazelles while the predation on mountain ungulates was predominantly post-midday. We provided three management implications for the recovery and restoration of cheetahs in Asia. Our work highlighted the importance of historical studies in informing the behavioral ecology of rare species.